2021
DOI: 10.3390/ijerph18073828
|View full text |Cite
|
Sign up to set email alerts
|

The Nexus between Urbanization and Traffic Accessibility in the Middle Reaches of the Yangtze River Urban Agglomerations, China

Abstract: China has entered the stage where urban agglomerations underpin and spearhead the county’s urbanization. Urban agglomerations in China have become economic growth poles, and the constantly improving transport networks in these agglomerations bring about opportunities for redistributing labor forces and promoting regional economic development, trade, and social progress for all. This is the foundation and fuel for urban development. However, lack of knowledge of the spatial features of, and the interrelationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 52 publications
0
19
0
Order By: Relevance
“…Generally, the establishment of national new areas is conducive to improve regional economic growth [ 62 ]. Some recent studies have empirically tested national new areas in a spatial agglomeration of economic activities, accelerating the urbanization and industrialization process in China [ 63 ]. Establishing the national new area is found to have increased the spatial inequality of the municipality where it is located, and the level of the regional economy, degree of openness, and complexity of administration has identified to be affected [ 13 ].…”
Section: Research Design Data and Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, the establishment of national new areas is conducive to improve regional economic growth [ 62 ]. Some recent studies have empirically tested national new areas in a spatial agglomeration of economic activities, accelerating the urbanization and industrialization process in China [ 63 ]. Establishing the national new area is found to have increased the spatial inequality of the municipality where it is located, and the level of the regional economy, degree of openness, and complexity of administration has identified to be affected [ 13 ].…”
Section: Research Design Data and Variablesmentioning
confidence: 99%
“…Therefore, firstly, PSM method is used, and control variables in the benchmark model are adopted to predict the probability of establishing the national new areas in each city through using Logit model. Secondly, the nearest neighbor matching method is used for sampling [ 63 ] what is put back, and then treatment and control groups are matched one-to-one. Finally, the mean difference between rematched treatment and control groups is examined, and the “pure effect” of policy implementation is assessed using the staggered DID method.…”
Section: Empirical Researchmentioning
confidence: 99%
“…The impact of logistics industry agglomeration on regional economy (van den Heuvel et al, 2013;Mori and Nishikimi, 2002;Chhetri et al, 2014;Rivera et al, 2014Rivera et al, , 2016Kayikci, 2010;Sheffi, 2012), logistics warehouse location and path optimization (Cheng et al, 2021;Liu and Ying, 2020;Shahparvari et al, 2020;Ferhat Candas and Kutanoglu, 2020;Alptekin et al, 2020;Zhang et al, 2021;Chen et al, 2021), and the research subject gradually changes from macro to individual. In addition to qualitative research, scholars also conduct research through various quantitative methods, mainly including vector autocorrelation and Granger causality test (Taniguchi and Van Der, 2000;Basatab, 2001;Hong -Oanh and Jose, 2010), DECD model (Skjott -Larsen et al, 2003;Camuthers et al, 2004a), time series (Mohammad, 2013;Sultan and Emrah, 2014), production function (Coto-Mill an et al, 2014) and spatial econometric model (Kumar et al, 2017;Peter and Catherine, 2018;Bai et al, 2022;He et al, 2019). The early research on logistics mainly focused on the relationship between logistics and economy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Bai, Dongling made a spatial analysis of China's logistics ecological efficiency and its influencing factors based on super SBM undesirable and spatial Dobbin model (Bai et al, 2022). Meiling he used panel data to study the temporal and spatial evolution of logistics enterprises in the Yangtze River Delta and found that logistics enterprises gradually transferred from the urban center to the suburbs (He et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…By introducing the spatial econometric regression model, the results showed that the spatial and temporal patter of urbanization was affected by internal source, administrative level and investment level. Similarly, Ge et al (2021) [ 5 ] evaluated the spatiotemporal distribution characteristics of urbanization levels and traffic accessibility with bivariate spatial autocorrelation model and spatial regression models. It was found that there existed a positive relation between urbanization level and traffic accessibility, but with a significant scale effect.…”
Section: Literature Reviewmentioning
confidence: 99%